Influence of Nanoparticle Processing on the Thermoelectric Properties of (BixSb1−X)2Te3 Ternary Alloys. Issue 2 (25th January 2021) - Salloum, Sarah; Bendt, Georg; Heidelmann, Markus; Loza, Kateryna; Bayesteh, Samaneh; Sepideh Izadi, M.; Kawulok, Patrick; He, Ran; Schlörb, Heike; Perez, Nicolas; Reith, Heiko; Nielsch, Kornelius; et al.
Abstract: The synthesis of phase‐pure ternary solutions of tetradymite‐type materials (Bix Sb1−x )2 Te3 (x=0.25; 0.50; 0.75) in an ionic liquid approach has been carried out. The nanoparticles are characterized by means of energy‐dispersive X‐ray spectroscopy (EDX), powder X‐ray diffraction (PXRD), scanning electron microscopy (SEM), and transmission electron microscopy. In addition, the role of different processing approaches on the thermoelectric properties ‐ Seebeck coefficient as well as electrical and thermal conductivity ‐ is demonstrated. Abstract : Tetradymite‐type ternary (Bix Sb1‐x )2 Te3 (x=0.25, 0.5, 0.75) nanoparticles were synthesized in an ionic‐liquid approach. The effect of thermal annealing on the chemical composition and morphology of the nanoparticles as well as their transport properties prior and after annealing is reported.